Current status and future prospects in biotic stress management in rice - Mohapatra, S D; Banerjee, Amrita; Senapati, R K; Prasanthi, G; Mohapatra, Minati; Nayak, P K; Nayak, A K; Maiti, D (ORYZA-An International Journal of Rice, 2021)
Insect pests and diseases are the major biotic constraints in rice production. According to the ecosystem, theÂ incidence of insect pests and diseases vary. The degree of loss due to different biotic stresses differ widelyÂ depending upon the predominant factors of abundance of these pests in a particular year, season or locality.Â Though around 800 insect species damaging rice in one way or another, the majority of them do very littleÂ damage. In India, about a dozen of insect species are of major pest status. Farmers bear an estimated average of 37% losses in rice crop due to insect pests and diseases every year. This review focuses on status of insect pestsÂ and diseases, extent of losses, different tools used in pest monitoring and management in rice. Among theÂ important pest management tools used in rice pest and diseases management are forecasting model for real-timeÂ pest-advisory services, light trap, hyper-spectral remote sensing, computer-based decision support system,Â disruptive technologies (mobile apps).